Prudential Regulation and Banking Efficiency in MENA Countries (Global Journal of Management and Business Research, 2018)
This paper analyses the impact of the prudential rules on bank efficiency and the relationship between profit efficiency and banking risks by introducing the financial and the macroeconomic determinants (real GDP growth rate, inflation, real GDP growth rate, inflation, the governance indicator ...). For this reason, we used a sample of 146 conventional banks in MENA countries during the 2003-2014 period, whose purpose was to determine the specificities of these countries concerning the determinants of profit efficiency.
Keywords: bank regulation; profit efficiency; MENA countries